Immunotherapy in prostate cancer: challenges and opportunities. (January 2016) - Noguchi, Masanori; Koga, Noriko; Moriya, Fukuko; Itoh, Kyogo
Although treatment options for castration-resistant prostate cancer (CRPC) have increased over the last decade, there remains a need for strategies that can provide durable disease control and long-term benefit. Recently, immunotherapy has emerged as a viable and attractive strategy for the treatment of CRPC. To date, there are multiple strategies to target the immune system, and several approaches including therapeutic cancer vaccines and immune checkpoint inhibitors have been most successful in clinical trials. With regard to this, we report the results of the most recent clinical trials investigating immunotherapy in CRPC and discuss the future development of immunotherapy for CRPC, as well as the potential importance of biomarkers in the future progress of this field.